Implementassi Pendekatan Realistic Mathematics Education (RME) di Sekolah Dasar - Fadiah Elwijaya; Mardiah Harun; Yullys Helsa (Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to analyze the application of Realistic Mathematics Education (RME) on fractions topic in elementary schools. The method used is a systematic literature review. The sample consisted of 32 primary studies on the effect of RME on Mathematics learning on fractions, which were drawn from all related studies. The study results were taken from indexed journals published in the 2016-2020 period. The key question in this research is how to describe the effect of RME on fraction material in elementary schools in terms of the study year, study level, research subject, research methodology, and research results. Through the systematic literature review method it was found that there had been an increase in research during the last 5 years. based on the level of study, research research in the higher class is more dominant, based on the duration of the majority. The research was conducted in elementary schools, and based on the number of samples, the research was conducted in classes with 20-30 subjects or more. Based on the results of the study, it was obtained data that there was an increase in still learning fraction topic using the RME approach.